A pooled analysis of post‐diagnosis lifestyle factors in association with late estrogen‐receptor–positive breast cancer prognosis. Issue 9 (9th December 2015) - Nechuta, Sarah; Chen, Wendy Y.; Cai, Hui; Poole, Elizabeth M.; Kwan, Marilyn L.; Flatt, Shirley W.; Patterson, Ruth E.; Pierce, John P.; Caan, Bette J.; Ou Shu, Xiao
Abstract : Lifestyle factors have been well studied in relation to breast cancer prognosis overall; however, associations of lifestyle and late outcomes (>5 years after diagnosis) have been much less studied, and no studies have focused on estrogen receptor‐positive (ER+) breast cancer survivors, who may have high risk of late recurrence and mortality. We utilized a large prospective pooling study to evaluate the associations of lifestyle factors with late recurrence and all‐cause mortality among 6, 295 5‐year ER+ Stage I–III breast cancer survivors. Pooled and harmonized data were available on clinical factors and lifestyle factors (pre‐ to post‐diagnosis weight change, body mass index (BMI) (kg/m 2 ), recreational physical activity, alcohol intake and smoking history), measured on average 2.1 years after diagnosis. Updated information for weight only was available. Study heterogeneity was evaluated by the Q‐statistic. Multivariable Cox regression models were stratified by study. Adjusting for clinical factors and potential confounders, ≥10% weight gain and obesity (BMI, 30–34.99 and ≥35) were associated with increased risk of late recurrence (hazard ratios (95% confidence intervals): 1.24 (1.00–1.53), 1.40 (1.05–1.86) and 1.41 (1.02–1.93), respectively). Daily alcohol intake was associated with late recurrence, 1.28 (1.01–1.62). Physical activity was inversely associated with late all‐cause mortality (0.81 (0.71–0.93) and 0.71 (0.61–0.82) for 4.9 to <17.4 and ≥17.4 metabolic equivalent‐hr/week). A U‐shaped association was observed for late all‐cause mortality and BMI using updated weight (1.42 (1.15–1.74) and 1.40 (1.09–1.81), <21.5 and ≥35, respectively). Smoking was associated with increased risk of late outcomes. In this large prospective pooling project, modifiable lifestyle factors were associated with late outcomes among long‐term ER+ breast cancer survivors. Abstract : What's new? Late recurrence is a major concern for women with ER+ breast cancer, which accounts for close to two‐thirds of diagnosed breast cancers. The factors that predispose survivors to late recurrence, however, are not fully understood. This report describes a role for certain lifestyle factors. Using pooled data from prospective cohorts, the authors' show that post‐diagnosis lifestyle factors, including alcohol intake, exercise, obesity and smoking, are associated with late breast cancer outcomes in estrogen receptor‐positive breast cancer survivors. The modifiable nature of these factors could have implications for long‐term survivorship care guidelines.